Dye Tracer Visualization of Infiltration Patterns in Soils on Relict Charcoal Hearths - Schneider, Anna; Hirsch, Florian; Raab, Alexandra; Raab, Thomas (Frontiers in Environmental Science, 2018)
Anthropogenically modified soils are often characterized by a high heterogeneity of substrates and show unique patterns of water infiltration. Such effects are not limited to intensively used or disturbed agricultural and technogenic soils, but can also occur as legacies of former land use in forested areas. The remains of historic charcoal hearths represent a widespread legacy of historic land use. Soils at relict charcoal hearths (RCHs) are most prominently altered by the deposition of a layer of charcoal-rich substrate on top of the natural soil surface. The presence of such a technogenic layer can considerably influence infiltration and soil wetness patterns on the sites. This study describes the spatial patterns of infiltration and soil wetness at charcoal hearth sites compared with undisturbed sandy forest soils for a historic charcoal production area north of Cottbus, Germany. We characterized six plots on RCH and reference soils under pine, oak and mixed forest by visualizing preferential flow patterns of infiltrating water in dye tracer experiments. Additionally, we characterized bulk density, soil organic matter contents and water repellency, using water drop penetration time (wdpt) tests, of the RCH and reference soil horizons. The results reflect that the persistence of water repellency of both the technogenic substrates and the natural topsoils is extremely high under dry conditions, but is drastically reduced after wet antecedent conditions. The dye tracer experiments reflect increased preferential flow on the RCHs for dry soil conditions, for which infiltration is limited to very few flow paths in the technogenic substrate layer. Differences between RCH and reference soils are less clear for higher antecedent soil wetness, for which the results indicate more uniform wetting of the technogenic substrates. We conclude that the structural properties of the additional technogenic substrate layer of RCHs have characteristic effects on water infiltration, causing a high temporal variation of preferential flow in relation to antecedent soil moisture conditions. These effects can result in high heterogeneity of soil moisture for dry conditions, and generally in a high temporal variation of soil wetness in RCHs soils.